Effects of different toothpastes on the prevention of erosion in composite resin and glass ionomer cement enamel and dentin restorations - Moda, Mariana Dias [UNESP] (2020)
Objective: This study aimed to evaluate the effects of different toothpastes on the surface wear of enamel, dentin, composite resin (CR), and resin-modified glass ionomer cement (RMGIC), and to perform a topographic analysis of the surfaces, based on representative images generated by atomic force microscopy (AFM) after erosion -abrasion cycles. Methodology: One hundred and forty bovine incisors were collected and divided into two groups: 72 enamel and 72 dentin blocks (4x4 mm). Half of the specimens were restored with CR (Filtek Z350 XT) and the other half with RMGIC (Fuji II LC). Then, samples were submitted to a demineralization cycle (5 days, 4x2 min/ day, 1% citric acid, pH 3.2) and exposed to three different toothpastes (2x15 s/day): without fluoride (WF, n=12), sodium fluoride -based (NaF, n=12), and stannous fluoride-based (SnF2, n=12). Surface wear, as well as restoration interfaces wear, were investigated by profilometry of the dental substrates and restorative materials. All representative surfaces underwent AFM analysis. Data were analyzed by two-way analysis of variance and Tukey's tests (alpha=0.05). Results: NaF-based toothpaste caused the greater dentin surface wear (p<0.05). Toothpastes affected only enamel-restoration interfaces. AFM analysis showed precipitate formation in dentinal tubules caused by the use of fluoride toothpastes. Conclusions: NaF-based toothpastes had no protective effect on enamel adjacent to CR and RMGIC against erosion abrasion-challenges, nor on dentin adjacent to RMGIC material. SnF2-based toothpastes caused more damage to interfaces between enamel and RMGIC.